The Effect of Menstruation On The Work Productivity of Women Employees At UD Kerupuk Singkong Nusantara Putra - Warter Agustim; Nur Ida Iriani; Yosefina Hariani (International Journal of Management and Business, 2025)
This study aims to analyze the effect of menstruation on the work productivity of female employees at UD Kerupuk Nusantara Putra, Batu City, with a quantitative approach through a survey method. The sample of this study was the entire population of female employees, totaling 60 people, selected using a saturated sampling technique. Data collection was carried out through observation, Likert-scale-based questionnaires, and documentation, then analyzed using simple linear regression to test the relationship between menstruation variables (independent) and work productivity (dependent). The results of the study indicate that menstruation has a significant effect on work productivity, where smooth and well-managed menstrual conditions contribute positively to employee efficiency and performance. Conversely, symptoms such as abdominal pain, cramps, and difficulty concentrating can be obstacles if not managed properly. Therefore, company support for the health of female employees during menstruation is very important in maintaining work performance. This study recommends the provision of supporting facilities such as special break rooms and flexible working hours to reduce productivity disruptions. In addition, this study encourages further exploration by adding other variables such as work environment, training, and motivation to provide a more comprehensive understanding of the factors that influence female employee productivity